Remote sensing and monitoring forest degradation by governmental entities in Brazil (Research, Society and Development, 2022)
The effective protection of native plant remnants present in Brazilian territory is one of the main contributions that the country must adopt in the Decade of Ecosystem Restoration (2021-2030) promulgated by the UN. The objective of the work was to present a general scenario of how governmental entities that deal with environmental protection can use digital platforms built from remote satellite data, as support for strategic planning aimed at controlling environmental degradation. Examples of successful databases that support the control of plant suppression and illegal forest fires are cited, such as Brazilian projects for issuing degradation alerts, such as DETER and PRODES of the National Institute for Space Research, and global platforms, such as Global Forest Watch with similar purposes. There was a presentation of a simple history of the use of geotechnological tools in the form of free data platforms, with data on vegetation cover. We present case studies of use of digital platforms incorporated in the environmental management of the State Public Ministry, such as the case of Mato Grosso, and the Federal Public Ministry. We emphasize the importance of the incorporation of technologies by public entities that promote synergies between the scientific and technological environment and the legal environment, in order to advance in the definition of protocols that bring more legal certainty, for the due validation of judicial evidence, which can effectively hold those who practice environmental illicit accountable.